Retinal Development and Pathophysiology in Kcnj13 Knockout Mice - Jiao, Xiaodong; Ma, Zhiwei; Lei, Jingqi; Liu, Pinghu; Cai, Xiaoyu; Shahi, Pawan K.; Chan, Chi-Chao; Fariss, Robert; Pattnaik, Bikash R.; Dong, Lijin; Hejtmancik, J. Fielding (Frontiers in Cell and Developmental Biology, 2022)
Purpose: We constructed and characterized knockout and conditional knockout mice for KCNJ13, encoding the inwardly rectifying K+ channel of the Kir superfamily Kir7.1, mutations in which cause both Snowflake Vitreoretinal Degeneration (SVD) and Retinitis pigmentosa (RP) to further elucidate the pathology of this disease and to develop a potential model system for gene therapy trials. Methods: A Kcnj13 knockout mouse line was constructed by inserting a gene trap cassette expressing beta-galactosidase flanked by FRT sites in intron 1 with LoxP sites flanking exon 2 and converted to a conditional knockout by FLP recombination followed by crossing with C57BL/6J mice having Cre driven by the VMD2 promoter. Lentiviral replacement of Kcnj13 was driven by the EF1a or VMD2 promoters. Results: Blue-Gal expression is evident in E12.5 brain ventricular choroid plexus, lens, neural retina layer, and anterior RPE. In the adult eye expression is seen in the ciliary body, RPE and choroid. Adult conditional Kcnj13 ko mice show loss of photoreceptors in the outer nuclear layer, inner nuclear layer thinning with loss of bipolar cells, and thinning and disruption of the outer plexiform layer, correlating with Cre expression in the overlying RPE which, although preserved, shows morphological disruption. Fundoscopy and OCT show signs of retinal degeneration consistent with the histology, and photopic and scotopic ERGs are decreased in amplitude or extinguished. Lentiviral based replacement of Kcnj13 resulted in increased ERG c- but not a- or b- wave amplitudes. Conclusions: Ocular KCNJ13 expression starts in the choroid, lens, ciliary body, and anterior retina, while later expression centers on the RPE with no/lower expression in the neuroretina. Although KCNJ13 expression is not required for survival of the RPE, it is necessary for RPE maintenance of the photoreceptors, and loss of the photoreceptor, outer plexiform, and outer nuclear layers occur in adult KCNJ13 cKO mice, concomitant with decreased amplitude and eventual extinguishing of the ERG and signs of retinitis pigmentosa on fundoscopy and OCT. Kcnj13 replacement resulting in recovery of the ERG c- but not a- and b- waves is consistent with the degree of photoreceptor degeneration seen on histology.